Vertigo and Ischemic Stroke after Hyperextension (Beauty Parlour Stroke syndrome) - Tosunoğlu, Bünyamin; Ünal, Sultan Merve; Aksoy, Seyfi Emre; Yoldaş, Tahir Kurtuluş (Acta medica Lituanica, 2022)
Beauty parlour stroke syndrome is a stroke syndrome that occurs secondary to hyperextension of the neck due to compression of the vertebral artery in the atlanto-occipital region. It was first defined as “pearl beauty stroke syndrome” in 1992 by Weintraub et al. Vertigo syndrome caused by cervical region pathologies, bad posture of the neck and/or trauma [1]. We present a young, 23-year-old patient who has no disease, no trauma history nor substance-drug use. He was diagnosed with vertigo that started after going to the barber’s and then had an infarction in the cerebellum.